Playing What Would You Do (WWYD) and Vocabulary-Drill: Its influence on Students’ Speaking Skills - Sigit Hartono; Nurbianta Nurbianta (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
English teaching is the main key to support the success of world interaction. The success in mastering English facilitates togetherness among people around the globe. Therefore freedom is needed in learning and understanding language as a whole. The teacher can use some methods in teaching and learning process to help the students’ understanding. In this research, the researcher practiced a game which is named What Would You Do (WWYD). This research problems were; (1) is there any influence of WWYD game to the students’ speaking skill at second semester of STIT Muhammadiyah, Tanjung Redeb?, (2) Is there any influence of drilling vocabulary to the students’ speaking skill at second semester of STIT Muhammadiyah, Tanjung Redeb?, and (3) Is there any influence of WWYD game and drilling vocabulary simultaneously to the students’ speaking skill at second semester of STIT Muhammadiyah Tanjung Redeb?. The method of this research is partial correlation method, specifically to find out whether WWYD game (i.e. independent variable/X1) and Drilling vocabularies (i.e. control variable/X2) have correlation to the students’ speaking skill (i.e. dependent variable/Y). In the end of this research shown that WWYD game and drilling vocabulary can facilitate and help the students getting a confident in speaking about their opinion in English, and the statistic value performed in level good correlation between WWYD game used to the students’ speaking skill during conducted for second semester at STIT Muhammadiyah Tanjung Redeb.